Predictors for Dividen Policy of Non-financial Corporations on the Indonesia Stock Exchange: OLS Method - Irfani, Agus S. (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 2, Agustus 2015 (pp. 113-216)DO - 10.24843/JEKT.2015.v08.i02.p05, 2015)
Number of previous studies in a variety of capital markets documenting that dividend policy was influenced by many variables including financial performance and firm size variables. However, these studies were still not provide consistent findings about the ability of the independent variables in predicting the dividend policy. The main objective of this study was to examine the effect of financial performance and firm size on dividend policy. The sample was set by adopting purposive sampling technique to have 50 companies of 390 non-financial companies listed on the Indonesia Stock Exchange that was regularly paying dividend during the period of 2010-2012. The hypothesis testing was conducted by emplyoing multiple linear regression technique. This study concluded that not all of the financial performance indicators shown to affect dividend payout ratio. Profitability dan firm size proved to have ability in explaining dividend payout ratio, but this study did not find any evidence that dividend payout ratio was affected by firm’s liquidity and solvability.
Keywords: liquidity, solvability, profitability, firm size, dividend payout ratio